2021
DOI: 10.1007/s11845-021-02838-2
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of TGFBI and TGFB2 in the plasma of gestational diabetes mellitus patients and its clinical significance

Abstract: Background Gestational diabetes mellitus (GDM) reflects a deficiency in the relative need for insulin during pregnancy, as well as temporary metabolic stress in the placenta and fetus. Our study aimed to research the potential diagnostic value of transforming growth factor-beta-induced protein ig-h3 (TGFBI) and transforming growth factor beta-2 proprotein (TGFB2) for GDM patients. Methods Online database Gene Expression Omnibus (GEO) was used to screen for different expressed genes (DEGs) associated with GDM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Our present results need to be confirmed in larger cohort of patient with stage IV PDAC in which the correlation between the [beta]ig-h3 tumor staining and serum level is to be explored, because tumor samples failed to be available for such experiment in this cohort owing to transfer/administrative constraints. It has been reported that in gestastional diabetes there was an increase of tgbi mRNA in the plasma [15]. Therefore, further investigation in correlation with other related physipathological states/diseases should be pursued.. Lastly, results from the ongoing stages I-III BIGHPANC cohorts will be of crucial importance to validate the increase in βig-h3 serum levels from stage I to stage IV.…”
Section: Discussionmentioning
confidence: 98%
“…Our present results need to be confirmed in larger cohort of patient with stage IV PDAC in which the correlation between the [beta]ig-h3 tumor staining and serum level is to be explored, because tumor samples failed to be available for such experiment in this cohort owing to transfer/administrative constraints. It has been reported that in gestastional diabetes there was an increase of tgbi mRNA in the plasma [15]. Therefore, further investigation in correlation with other related physipathological states/diseases should be pursued.. Lastly, results from the ongoing stages I-III BIGHPANC cohorts will be of crucial importance to validate the increase in βig-h3 serum levels from stage I to stage IV.…”
Section: Discussionmentioning
confidence: 98%
“…87 Similarly, Zhou et al also found that the expression of TGFBI was upregulated in the placenta and plasma of patients with gestational diabetes, which is a state of low-grade systemic inflammation, 88 compared to that in the corresponding samples obtained from healthy controls. 89 Of note, in the context of PTL induced by uterine overdistention, Adams et al…”
Section: Discussionmentioning
confidence: 99%
“…COL4A1 was involved in diabetic tubulointerstitial injury (Zeng et al, 2019) and COL5A2 participated in the progression of uterine fibroids (Giri et al, 2017) and colon adenocarcinoma (Wei et al, 2020), although their functions were not fully understood for GDM development. TGFBI, upregulated in the placenta and the plasma of GDM, was positively associated with FBG levels in GDM patients (Han et al, 2014;Zhou et al, 2021). SLC7A5 enables L-leucine/L-tryptophan transmembrane transporter activity and is a part of amino acid transport complex.…”
Section: Discussionmentioning
confidence: 99%
“…TGFB2 encodes a secreted ligand of the transforming growth factor-beta (TGF-β) superfamily of proteins, which is involved in the pathogenesis of diabetes and complications. Zhou et al reported that TGFB2 is an upregulated gene in the plasma of GDM patients and correlated with FBG levels in GDM patients ( Zhou et al, 2021 ), which suggested that TGFB2 might play vital roles in the pathogenesis of GDM. FBN2 encodes a peptide hormone placensin, which stimulates cAMP-PKA signaling, glucose secretion and trophoblast invasion in human trophoblastic cells.…”
Section: Discussionmentioning
confidence: 99%